Modern principles of constipation treatment - M. A. Livzan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
The aim of review. To present up-to-date approach to prescription of laxatives at treatment of constipation.Original positions. The laxatives are agents with the various mode of action. At incidentally developing constipation stimulative laxatives are most effective. Presence of рН-dependent coating due to which the active substance is delivered to the large intestine, and also predictive time of the effect onset and safety profile make dulcolax (Bisacodyl) an agent of choice among drugs of this group. At chronic constipation with necessity of prolonged treatment the best results of treatment are obtained at application of osmotic laxatives which in case of resistant constipation are prescribed in combination with stimulative purging.Conclusion. Laxatives prescription should be differentiated with account of differences in mechanisms of their action.